CASE BASED REASONING UNTUK MENDIAGNOSA PENYAKIT KEHAMILAN MENGGUNAKAN COSINE SIMILARITY - Adelysa P Gitaswara; Sebastianus Adi Santoso Mola; Emerensiana S.Y Pandie (J-Icon : Jurnal Komputer dan Informatika, 2017)
The application of case-based reasoning in diagnosing pregnancy deseases is motivated by the lack of number of obstetricians. The use of CBR aims to solve new problems by adapting the solutions contained in the previous case, by calculating the level of similarity. Calculation of similarity value using cosine similarity method, with threshold equal to 100%. This system can diagnose 6 diseases, 28 existing symptoms. System outbreaks of illness experienced by patients based on symptoms induced by non-specialist medical personnel, as well as handling solutions accompanied by a presentation of similarities with previous cases to indicate the degree of truth of possible diagnosis. Based on the results of case testing, the results obtained: the system can retrieve the exact old case and have used the cosine similarity methodology correctly, shown with 100% accuracy results, and using 104 cases is optimal enough to diagnose 6 illnesses shown with average results Similarity to 20 cases is 90%.